2023
DOI: 10.1155/2023/6841344
|View full text |Cite|
|
Sign up to set email alerts
|

Relationship between Platelet-to-Lymphocyte Ratio and Lymphocyte-to-Monocyte Ratio with Spontaneous Preterm Birth: A Systematic Review and Meta-analysis

Abstract: Background. Spontaneous preterm birth is one of the most common pregnancy complications in obstetric clinical practice, and its etiology is complex. The problems of low survival and high morbidity rates of premature infants need to be solved urgently. The platelet-to-lymphocyte ratio (PLR) and lymphocyte-to-monocyte ratio (LMR) are two novel biomarkers of inflammation, and several studies have linked PLR and LMR to spontaneous preterm birth. These systematic review and meta-analysis are aimed at analyzing the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%